Maternal uterine natural killer cells nurture fetal growth: in medio stat virtus. Issue 2 (February 2015) - Colucci, Francesco; Kieckbusch, Jens
Highlights Maternal immune responses need not be generally suppressed during pregnancy. Adequate activation of uterine natural killer cells impacts on birth weight.